Synthesizing the strontium carbonate and silver doped bioceramic bone graft: Structure-properties and cell viability - Uemirel, Mehtap; Kaya, Ali, I; Aksakal, Bunyamin (WILEY, 2020)
An alternative bioceramic bone graft was synthesized through the sol-gel method by substituting strontium carbonate-SrCO3 and Silver-Ag into Ca(NO3)(2)center dot 4H(2)O, KOH, NaNO3, P2O5, and urea compounds. Morphological properties of the fabricated grafts were characterized by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy (SEM). Mechanical properties were determined via the hardness and compression tests. Furthermore, the cell viability of fabricated biografts was also determined via cytotoxicity tests using the MTS (cell proliferation assay). FTIR, EDS, and XRD analyses indicated that SrCO3- and Ag-substituted hydroxyapatite (Sr/Ag/HA) biograft fabrications were achieved. SEM images of the biografts showed that a low-porous structure was formed with grains bonded through sintering. SEM images also revealed that the powder bonding increased due to the decrease in pore sizes when the amount of SrCO3 was increased. From the mechanical tests, it was obtained that, the strength and hardness increased with increased SrCO3 rates. Through the cytotoxicity tests, it was shown that the cell viability rate increased due to the presence of SrCO3 and no toxic effects were observed through the newly synthesized biografts.
Keywords: biograft; cytotoxicity; mechanical properties; sol-gel; strontium carbonate-SrCO3; SUBSTITUTED HYDROXYAPATITE; PHOSPHATE; CEMENT; OSTEOBLAST; SR; Materials Science